EFL LEARNERS’ PREFERENCES AND PERSPECTIVES ON LEARNING STYLES - Norhasanah, Norhasanah; Yusuf, Fazri Nur; Suherdi, Didi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Learning styles have become a growing issue in the pedagogical area and have been explored by many studies in recent years. The concepts and theories of learning styles could have significant implications for designing teaching instruction. Thus, this study aims to identify students’ learning styles preferences and their perspectives on learning styles in the English learning context. Particularly, it investigates students’ choices of learning styles and how they perceive their learning styles in learning practice. It was conducted in the survey research using VAK Learning Styles Self-Assessment Questionnaire, followed by some open-ended and close-ended questions to see students’ perspectives on Learning Styles involving 44 respondents. The data were analyzed using descriptive statistical analysis. Results indicate that students’ learning styles varied, but the highest percentage, 39 percent of students preferred to learn through visuals. Related to students’ perspectives, most of them were quite aware of their learning style, but unfortunately, 45.5 percent of them stated that their English learning was not yet suitable with their learning style; this can be a reflection for all of us. With all these results, this study was expected to give little information and description related to students’ learning styles preferences and perspectives.